2014
DOI: 10.1016/j.jcte.2014.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Patient and parent perceptions of the diagnosis and management of cystic fibrosis-related diabetes

Abstract: BackgroundCystic Fibrosis Related Diabetes (CFRD) is an increasingly common complication in CF. CFRD introduces an additional complex chronic disease to individuals already attending to demanding treatment regimens. An improved understanding of the reaction to and coping mechanisms surrounding CFRD may facilitate management of CFRD.MethodsSemi-structured interviews completed by 10 children with CFRD, 10 adults with CFRD and 10 parents of children with CFRD in a single large CF Care Center were analyzed utilizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…Despite the fact that CFRD now affects nearly half of adults with CF, many studies have shown that the association between CF and CFRD is still not well recognized. In fact, only 50% of individuals participating in semi-structured interviews were even aware that CFRD was possible [2] , [3] . Furthermore, many individuals use experiences of family members, friends or acquaintances with other types of diabetes to frame their knowledge of CFRD [2] , [4] , [5] .…”
Section: Awareness and Understanding Of Cfrdmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that CFRD now affects nearly half of adults with CF, many studies have shown that the association between CF and CFRD is still not well recognized. In fact, only 50% of individuals participating in semi-structured interviews were even aware that CFRD was possible [2] , [3] . Furthermore, many individuals use experiences of family members, friends or acquaintances with other types of diabetes to frame their knowledge of CFRD [2] , [4] , [5] .…”
Section: Awareness and Understanding Of Cfrdmentioning
confidence: 99%
“…In fact, only 50% of individuals participating in semi-structured interviews were even aware that CFRD was possible [2] , [3] . Furthermore, many individuals use experiences of family members, friends or acquaintances with other types of diabetes to frame their knowledge of CFRD [2] , [4] , [5] . For example, in a study by Dashiff et al, up to 40% of adolescents with CFRD compared it to other types of diabetes.…”
Section: Awareness and Understanding Of Cfrdmentioning
confidence: 99%
“…It is important to find physicians who were knowledgeable about both CF and diabetes. According to the data, improvement in lung function associated with better diabetes control was motivating for patients [25].…”
Section: Clinical Case #mentioning
confidence: 99%
“…Adding to the difficulty is the observation that approximately half of CF individuals are not aware of the possibility of developing CFRD as a complication of CF. 97,99 To avoid patients feeling blind-sighted by the diagnosis of CFRD, CF caregivers might introduce the possibility of CFRD development as a common complication in CF at an earlier age. This can be achieved through educational materials, family/patient education events, and interaction with experts in CFRD.…”
Section: Quality Of Lifementioning
confidence: 99%